Aims in ELT. A comparison study between Yemen and the Czech Republic. - Ibrahim, Khadija (Univerzita Pardubice, 2017)
This diploma paper deals mainly with aims of English language teaching. The investigation primarily aims at determining and comparing the aims of ELT specified for the Secondary Education in both countries, Yemen and the Czech Republic. Therefore, it is an attempt to examine if these aims are clearly stated as well as to explore in which curricular document they are exactly stated. Furthermore, it tries to explore and points out the general aims represented in the key competencies. It is worth noting that, the comparison between both countries is to determine the similarities and the differences between them.
Cíle v ELT. Komparativní studie zaměřená na srovnání Jemenu a České republiky.
Keywords: výukové cíle; kurikulární dokumenty; Jemen; Česká republika; komparativní studie; Bloomova taxonomie cílů; aims; ELT; curricular documents; Yemen; Czech Republic; comparative study; Bloom's revised taxonomy